Import Protection, Business Cycles, and Exchange Rates : Evidence from the Great Recession - Bown, Chad P.; Crowley, Meredith A. (World Bank, Washington, DC, 2012)
This research estimates the impact of macroeconomic fluctuations on import protection policies over 1988:Q1-2010:Q4 for the United States, European Union, and three other industrialized economies. First, estimates on a pre-Great Recession sample provide evidence of three key relationships for the US and EU. Increases in domestic unemployment rates and real appreciations in bilateral exchange rates led to substantial increases in antidumping and related forms of import protection. Furthermore, economies historically imposed these bilateral import restrictions on trading partners going through their own periods of weak economic growth. Second, estimates from the pre-Great Recession model predict a major trade policy response during 2008:Q4-2010:Q4, given the realized macroeconomic shocks. New US and EU trade barriers were projected to cover up to an additional 15 percentage points of nonoil imports, well above the baseline level of 2-3 percent of import coverage immediately preceding the crisis. Third, re-estimating the model on data from the Great Recession period illustrates why the realized trade policy response differed from model predictions based on historical data. While exchange rate movements played an important role in limiting new import protection, the US and EU also "switched" from their historical behavior during the Great Recession and shifted new import protection toward trading partners experiencing economic growth and away from those that were contracting.